Hypanus dipterurus - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Hypanus dipterurus (Jordan & Gilbert, 1880). Bullseye Stingray, Diamond Stingray, Shorttail Stingray, or Whiptail Stingray. To 200 cm (78.7 in) TL (Grove and Lavenberg 1997); 122 cm (48 in) DW (Robertson and Allen 2008). Malibu, southern California (Christopher Lowe, pers. comm. to M.L.) to northern Chile and Islas Galápagos (Grove and Lavenberg 1997), including Gulf of California (McEachran in Fischer et al. 1995); Hawaiian Islands (Last et al. 2016). Unverified captures off British Columbia and central California. Benthic; depth: intertidal to at least 150 m (492 ft) (Carlise et al. 1960; Weigman 2016), and perhaps to 355 m (1,164 ft) (Mundy 2005). Previously as Dasyatis dipterura (Jordan & Gilbert, 1880), we follow Last et al. (2016) and use the genus name Hypanus . Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 28, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008